Análisis del impacto socioeconómico de cisticercosis humana y epilepsia relacionada a neurocisticercosis, en la provincia de Pichincha - Aguirre Saá, Rafaela Alejandra (2018)
Cysticercosis is a parasitic disease included in the list of Neglected Tropical Diseases. The main problem with diseases such as cysticercosis, lies in the great economic losses that are generated by the disease; sequelae (e.g. epilepsy related to neurocysticercosis) that this can generate in patients. The World Health Organization mentions that these diseases affect billion people worldwide, where populations living in close contact with vectors and animals, are manly affected. Ecuador is an endemic country for cysticercosis. From 2005 to 2015, a total of 1,033 cases of cysticercosis and 6,693 cases of epilepsy were reported, a characteristic sequel to cysticercosis, in the province of Pichincha. The number of cases obtained implied an average loss of 3,285DALYs due to cysticercosis and an average loss of 24,408 DALYs due to epilepsy. The DALYs obtained in the study generated an approximate total of expenses: cysticercosis: minimum: 14.012,663.66 dollars; maximum: 17.290,542.80 dollars; epilepsy: minimum: 107.026,440.90 dollars; maximum: 133.646,359.80 dollars. The monetary losses resulting from the presence of diseases in Pichincha presented considerable losses. Although the study shows estimated data, it is necessary to consider the ranges of present losses and to recognize that the disease of the study is not the only one present in the country; it is not the only disease in Ecuador that generates economic losses.